Sarau: um ritual da voz - Cruz Filha, Fernanda (2018)
This work is the result of a study of the soirée as a ritual performance and as an aggregator space your sociocultural perspective. Part of the approach of this dissertation, the construction of a brief history of your occurrence in Brazil and your consolidation as democratic space of exchanges and strengthening of social groups. The presente work chooses the Soirée of “Minas” (slang for women in Brazil), from Goiânia- GO, which takes place since of the year 2016, organized by women as a itinerante soirée, for an analysis of content on the social representation of this cultural manifestation. We tried to discuss here the space of speech, poetry, listening and welcoming women. It is hoped that with the realization of this research, the space for so many voices that have been in this territory for a long time cultivated, which is the soirée, will be even more open. The poetry of the voices echo in the corners wide your aggregating and transformative force.